As the Witnesses Fall Silent: 21st Century Holocaust Education in Curriculum, Policy and Practice - Gross, Zehavit (Springer, 2016)
This volume represents the most comprehensive collection ever produced of empirical research on Holocaust education around the world. It comes at a critical time, as the world observes the 70th anniversary of the liberation of Auschwitz. We are now at a turning point, as the generations that witnessed and survived the Shoah are slowly passing on. Governments are charged with ensuring that this defining event of the 20th century takes its rightful place in the schooling and the historical consciousness of their peoples. The policies and practices of Holocaust education around the world are as diverse as the countries that grapple with its history and its meaning. Educators around the globe struggle to reconcile national histories and memories with the international realities of the Holocaust and its implications for the present. These efforts take place at a time when scholarship about the Holocaust itself has made great strides. In this book, these issues are framed by some of the leading voices in the field, including Elie Wiesel and Yehuda Bauer, and then explored by many distinguished scholars who represent a wide range of expertise. Holocaust education is of such significance, so rich in meaning, so powerful in content, and so diverse in practice that the need for extensive, high-quality empirical research is critical. Th is book provides exactly that.